METODE MIND MAPPING DIGITAL: EFEKTIFKAH TERHADAP HASIL BELAJAR? - Mufidah, Zalfa; Arie Rakhmat Riyadi; Faisal Sadam Murron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the digital mind mapping method on students' learning outcomes in Grade IV Phase B on the topic of rules and norms in elementary school. This research uses a quantitative approach with a pre-experimental method, and the sample was selected using purposive sampling consisting of 19 students. The research instruments used were pre-tests and post-tests, and the data were analyzed using linear regression analysis, paired t-test, and the N-Gain score difference test. The results of the study showed a linear regression result of 67%, a paired t-test value of p = 0.001, and an N-Gain score difference of 0.74. These findings indicate that the mind mapping method is effective significantly improving students' learning outcomes in the topic of rules and norms in Grade IV Phase B of elementary school.